Exploring local wisdom-based arabic language environment practices and their contribution to students’ speaking proficiency - Hamdy M. Zen; Nila Sari Taha (12 Waiheru, 2026)
This study examines innovative strategies for creating an Arabic language environment based on local wisdom at State Islamic Senior High School (MAN) 1 North Halmahera. Using a descriptive qualitative approach, this research investigates the implementation of local cultural integration in Arabic language learning and its impact on students' speaking skills. The research findings demonstrate significant improvement in students' speaking abilities through a contextual approach that connects Arabic language with local cultural contexts. The methods used in this study include in-depth interviews, participatory observation, and document analysis. The findings indicate that the integration of local wisdom through folklore, regional songs, and cultural activities can enhance students' motivation and speaking competence, with speaking skills percentages increasing from an average of 35-45% to 70-80%. This research provides theoretical contributions to the development of foreign language learning models based on local culture.